Evaluating the Effects of Cu2+ on the Development and Reproduction of Spodoptera litura (Lepidoptera: Noctuidae) Based on the Age-Stage, Two-Sex Life Table. Issue 6 (25th November 2022) - Yang, Yang; Qi, Jingwei; Wang, Zailing; Zhou, Zhixiong; Zhao, Changwei; Dong, Xiaolin; Li, Xihong; Li, Chuanren
Abstract: Copper (Cu 2+ ) is a micronutrient that promotes the development and reproduction of organisms. However, with the rapid expansion of modern industry and agriculture, Cu 2+ concentrations are increasing, which might have negative impacts on biological and ecological safety. Spodoptera litura is not only an intermittent outbreak pest but also can be used as a model organism to assess environmental and ecological risks. Therefore, the effects of the life history and population parameters of S. litura fed on artificial diets with different Cu 2+ concentrations were analyzed using the age-stage, two-sex life table. Our results showed that not only the preadult survival rate but also the intrinsic rate of increase ( r ) and the finite rate of increase ( λ ) were significantly increased under exposure to low Cu 2+ concentrations (2, 4, and 8 mg/kg). In addition, the population growth of S. litura was significantly faster, indicating that S. litura can adapt well to low concentrations and is likely to undergo outbreaks of damage. Whereas, in addition to a significant reduction in preadult survival rate, population growth rate, pupal weight, pupal length, adult body weight, and oviposition were also significantly reduced under exposure to high Cu 2+ concentration (32 mg/kg). And when the concentration reached 64 mg/kg, the survival rate of adults was extremely low, suggesting a decrease in the adaptation of S. litura . These results can help to understand the population dynamics of S. litura and predict potential ecological risks.